Korelasi Kepercayaan Diri dan Efikasi Diri Akademik Mahasiswa Program Studi Bimbingan Dan Konseling Angkatan 2018 - Eklys Cheseda Makaria; Ali Rachman; Ririanti Rachmayanie J (Universitas Kanjuruhan Malang, 2019)
This study aims to describe the relationship between self-confidence and academic self-efficacy in students of the Lambung Mangkurat University Guidance and Counseling study program in 2018. The sample in this study amounted to 102 students. Data were collected using the academic self-efficacy scale and self-confidence scale, and analyzed using SPSS 20. Data analysis was performed using Pearson Corelation Product Moment analysis. The results showed that there was a relationship between academic self-efficacy and student self-confidence.